Information and Communication Technology Skills Dynamics in Mozambique - Canani, Ammar (Department of Information Systems, 2025)
The current state of Information and Communication Technology (ICT) in Mozambique is inadequate in terms of education, skills, infrastructure, government support, language, and culture. There is poor education available at all levels, and there is a lack of basic ICT skills countrywide. Language and cultural differences constitute barriers to ICT, due to English not being commonly spoken. The infrastructure of the country remains insufficient to fully reap the potential of ICT. As there is insufficient literature regarding ICT as a field in Mozambique , this study lays some of the groundwork in this regard, by inductively exploring the dynamics around ICT skills supply and demand, as perceived by local actors. The study was guided by a Case Study-Grounded Theory Methodology (CS-GTM), with data collected through in-depth interviews with various local stakeholders implicated in the ICT skills ecosystems. The findings reveal a never-ending loop of a lack of the supply of ICT opportunities (employment, education, and training) to gain ICT skills on the one hand, and a lack of skills available to demand ICT skills in the country as a result of the lack of current conditions for ICT growth, aided by a lack of support from the government for ICT on the other . Some of the dynamics raised were the centralisation and reliance on the capital city, the hierarchy of the different regions of the country, and the heavy reliance on foreign companies and talent. From a big picture view, the government holds the power in the ICT ecosystem but provides little support leading to stakeholders adapting to the situation. However, due little support, ICT skills supply remain inadequate leading to inadequate demand creating a never-end loop of ICT skills not improving in the ecosystem. For future research, studying the role of the government may assist in better understanding the different dynamics at play. Interviewing participants from the different parts of the country will broaden understanding. Lastly, comparing the dynamics in Mozambique to dynamics in similar countries (in terms of development indicators) may provide further insight.